Correlates of perceived stress with anxiety symptoms sleep quality and academic performance among Moroccan students - Hakima EL Madani, PhD; Chadya Aarab; Nabil Tachfouti; Samira EL Fakir; Rachid Aalouane; Mohamed Berraho (Educación Médica)
Introduction: The main objective of this study was to verify the association of perceived stress with anxiety, sleep quality, and academic performance among Moroccan medical students. Methods: This cross-sectional study included 222 students enrolled at the Faculty of Medicine and Pharmacy of Fez in Morocco. An online self-administrated questionnaire, for the sociodemographic characteristics, Perceived Stress Scale (PSS-10), Test Anxiety Scale, and Pittsburgh Sleep Quality Index questionnaire were used for the assessment. A descriptive and correlational design was used in this investigation. Results: One hundred and thirty-two students completed the survey. A high level of stress was found. A significant positive correlation was observed between the stress level among our population and their levels of anxiety. Stress was also positively correlated with the decrease of students’ sleep quality and academic performance. Conclusion: The results of this investigation present worthy data that highlight the need for this subset of students to anti-stress programs that must be integrated into their curriculum to help them to better manage this psychological issue. Resumen: Introducción: El principal objetivo de este estudio fue verificar la asociación del estrés percibido con la ansiedad, la calidad del sueño y el rendimiento académico entre estudiantes de medicina marroquíes. Métodos: Este estudio transversal incluyó a 222 estudiantes matriculados en la Facultad de Medicina y Farmacia de Fez en Marruecos. Para la evaluación se utilizó un cuestionario autoadministrado en línea para las características sociodemográficas, la Escala de estrés percibido (PSS-10), la Escala de ansiedad ante los exámenes y el cuestionario del Índice de calidad del sueño de Pittsburgh. En esta investigación se utilizó un diseño descriptivo y correlacional. Resultados: Ciento treinta y dos estudiantes completaron la encuesta. Se encontró un alto nivel de estrés. Hubo una correlación positiva significativa entre los niveles de estrés y ansiedad. El estrés también se correlacionó positivamente con la disminución de la calidad del sueño y el rendimiento académico de los estudiantes. Conclusión: Los resultados de esta investigación presentan datos valiosos que resaltan la necesidad de que este subconjunto de estudiantes reciba programas antiestrés que deben integrarse en su plan de estudios para ayudarlos a gestionar mejor este problema psicológico.